Identifying Trends In Job Hopping In Private Institutions Of Higher Learning (INTERNATIONAL JOURNAL OF MANAGEMENT & INFORMATION TECHNOLOGY, 2013)
Since early 20th century, there is greater mobility among academicians in the private institutions of higher learning in Malaysia. The high turnover is the result of economical and social changes in the country. With globalization, Malaysia has now become a hub for international education. This has led to the growth in private institutions of higher learning. With the vast increase in such institutions, employees today have greater opportunities to job hop for various reasons. This research paper investigated the emerging trends in job hopping and the reasons behind it. The reasons were attributed to intrinsic and extrinsic motivating factors. The research further investigated whether there are differences in the trends between the various age groups; Baby Boomers (48 years and above), Generation X (33-47 years) and Generation Y (32 years and below). The researchers were motivated to do this research due to the increasing concern over the drastic mobility that is taking place in the private institutions of higher learning. The sample for this research comprised of 100 academicians working in private institutions of higher learning. Participants were given questionnaires to obtain responses on the intrinsic and extrinsic motivating factors leading to their decision to job hop. The selection of participants was based on a purposive sampling method as the researchers wanted to obtain responses from the three categories of generation. The findings proved the key hypothesis of the research which is; firstly, there is a trend in the job hopping exercise in the private institutions of higher learning and secondly, there are differences in the trends between the three categories of generations. The researchers went on to offer practical suggestions to the private institutions of higher learning and the Ministry of Human Resources in Malaysia to establish guidelines and policies to ensure that the job hopping practice is kept to the minimum.